2021
DOI: 10.3390/biomedicines9080892
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Functional Adrenocortical Adenoma and Carcinoma: Genetic Characterization and Intracellular Signaling Pathway

Abstract: The adrenal cortex produces steroid hormones as adrenocortical hormones in the body, secreting mineralocorticoids, glucocorticoids, and adrenal androgens, which are all considered essential for life. Adrenocortical tumors harbor divergent hormonal activity, frequently with steroid excess, and disrupt homeostasis of the body. Aldosterone-producing adenomas (APAs) cause primary aldosteronism (PA), and cortisol-producing adenomas (CPAs) are the primary cause of Cushing’s syndrome. In addition, adrenocortical carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…transcription factors inhibits the transcriptional activity of MEN1, thereby contributing to tumor growth. Both of the above mechanisms have been confirmed as components of ACC pathogenesis [9]. Calcium ions play a crucial role in the synthesis and release of the adrenal cortex hormone, and alterations in the intracellular calcium ion concentration following cellular depolarization stimulate the production of hormones such as aldosterone [10].…”
Section: Discussionmentioning
confidence: 94%
“…transcription factors inhibits the transcriptional activity of MEN1, thereby contributing to tumor growth. Both of the above mechanisms have been confirmed as components of ACC pathogenesis [9]. Calcium ions play a crucial role in the synthesis and release of the adrenal cortex hormone, and alterations in the intracellular calcium ion concentration following cellular depolarization stimulate the production of hormones such as aldosterone [10].…”
Section: Discussionmentioning
confidence: 94%
“…Here, the majority of variants involved in APAs are deletions within a specific region of the M4 domain which is involved in binding of Ca 2+ and ion gating [115,116,118,122,123,126,127,140,145,146]. In vitro studies have shown that ATP2B3 variants increase production of aldosterone by decreasing export of Ca 2+ (due to loss of the pump function) leading to increased intracellular concentration of Ca 2+ , membrane depolarization, and activation of calcium signaling [147,148].…”
Section: Aldosterone-producing Adrenocortical Adenomasmentioning
confidence: 99%
“…[13] Only a few patients with ACC are associated with familial genetic disorders, while disseminated cases are associated with mutations in various genes such as tumor protein p53, catenin beta like 1, menin 1, and cyclin dependent kinase inhibitor 2A. [17][18][19] However, the specific pathogenic mechanism of ACC remains unclear. Hence, exploring the diagnostic markers and therapeutic targets for ACC is urgent.…”
Section: Introductionmentioning
confidence: 99%